Religion, death and the senses - Welch, Christina; Shadrack, Jasmine Hazel (Religion and the senses, 2024)
"The uniqueness of this collection lies in two areas, firstly its deep engagement with a range of physical and socio-cultural sensual responses to death and dying, and secondly, through its contributors who are drawn from a wide spectrum of professional, practical, and theoretical expertise and scholarship in fields which continue to redefine our understanding of mortality"--